ATTITUDES OF FUTURE PRESCHOOL TEACHERS TOWARDS THE IMPORTANCE OF MUSIC EDUCATION FOR PRESCHOOL CHILDREN - Đuragić, Nataša (Norma, 2024)
The paper deals with the presentation of the attitudes of students of the Preschool Teachers Training College in Novi Sad regarding the importance of musical education for preschool children, and the examination of potential correlates of those attitudes in the form of previous musical education or experience, the family’s cultural and pedagogical climate and sociodemographic factors. The research approach as well as the results are presented in two parts. The first part of the research was conducted on a sample of 225 second- and third-year students of the Preschool Teachers Training College in Novi Sad. The research was conducted using a non-experimental type method, surveying and scaling techniques, with instruments specially constructed for the needs of this research. The results of the research show that students express very positive attitudes towards the importance of music education for children of preschool age, but that there are differences between the level of positivity of the attitudes of students in the second and third year of study. The second part of the research is a qualitative research, which aims to examine the causes of the difference in attitudes between second and third year students, the change in interest in music and music-performance subjects during the course of study, as well as to what extent the syllabus of music-performance subjects has been changed and supplemented influenced the mentioned differences. One of the goals of the research was to examine the role of teachers in the formation and further affirmation of students’ attitudes towards the importance of music education. The research was conducted on a sample of 50 students, and it was done using the technique of surveying and content analysis. Content analysis showed that the majority of students perceive the changes in the syllabus positively due to the increase in professional competences and feelings of personal satisfaction and self-achievement. Also, most students see the teacher as a key figure in realizing and improving their own musical potential. The obtained results open up a space for designing a program to increase the musical and performance competencies of preschool students, so that in the future they could provide adequate musical stimulation to children in preschool institutions.